Combating Intracellular Pathogens with Nanohybrid-Facilitated Antibiotic Delivery - Bose RJC (Dove Medical Press, 2020)
Rajendran JC Bose,1– 4,* Nagendran Tharmalingam,5,* Yonghyun Choi,1 Thiagarajan Madheswaran,6 Ramasamy Paulmurugan,2,3 Jason R McCarthy,4 Soo-Hong Lee,7 Hansoo Park1 1School of Integrative Engineering, Chung-Ang University, Seoul, South Korea; 2Molecular Imaging Program at Stanford (MIPS), Department of Radiology, School of Medicine, Stanford University, Stanford, CA 94305-5427, USA; 3Canary Center at Stanford for Cancer Early Detection, Department of Radiology, School of Medicine, Stanford University, Stanford, CA 94305-5427, USA; 4Masonic Medical Research Institute, Utica, NY, USA; 5Infectious Diseases Division, Warren Alpert Medical School of Brown University, Rhode Island Hospital, Providence, RI 02903, USA; 6Department of Pharmaceutical Technology, School of Pharmacy, International Medical University, Kuala Lumpur 57000, Malaysia; 7Department of Medical Biotechnology, Dongguk University, Seoul, Gyeonggi-do, South Korea*These authors contributed equally to this workCorrespondence: Soo-Hong Lee Department of Medical BiotechnologyDongguk University, Seoul, Gyeonggi-do, South KoreaTel +82-31-961-5153Email soohong@dongguk.eduHansoo ParkSchool of Integrative Engineering, Chung-Ang University, Seoul, South KoreaTel +82 2-820-5804Email heyshoo@cau.ac.krBackground: Lipid polymer hybrid nanoparticles (LPHNPs) have been widely investigated in drug and gene delivery as well as in medical imaging. A knowledge of lipid-based surface engineering and its effects on how the physicochemical properties of LPHNPs affect the cell–nanoparticle interactions, and consequently how it influences the cytological response, is in high demand.Methods: Herein, we have engineered antibiotic-loaded (doxycycline or vancomycin) LPHNPs with cationic and zwitterionic lipids and examined the effects on their physicochemical characteristics (size and charge), antibiotic entrapment efficiency, and the in vitro intracellular bacterial killing efficiency against Mycobacterium smegmatis or Staphylococcus aureus infected macrophages.Results: The incorporation of cationic or zwitterionic lipids in the LPHNP formulation resulted in a size reduction in LPHNPs formulations and shifted the surface charge of bare NPs towards positive or neutral values. Also observed were influences on the drug incorporation efficiency and modulation of the drug release from the biodegradable polymeric core. The therapeutic efficacy of LPHNPs loaded with vancomycin was improved as its minimum inhibitory concentration (MIC) (2 μg/mL) versus free vancomycin (4 μg/mL). Importantly, our results show a direct relationship between the cationic surface nature of LPHNPs and its intracellular bacterial killing efficiency as the cationic doxycycline or vancomycin loaded LPHNPs reduced 4 or 3 log CFU respectively versus the untreated controls.Conclusion: In our study, modulation of surface charge in the nanomaterial formulation increased macrophage uptake and intracellular bacterial killing efficiency of LPHNPs loaded with antibiotics, suggesting alternate way for optimizing their use in biomedical applications.Keywords: nanohybrids, intracellular bacterial infection, Mycobacterium smegmatis, Staphylococcus aureus, doxycycline, vancomycin